2014
DOI: 10.1515/hf-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and abiotic decay in waterlogged archaeological Picea abies (L.) Karst studied by confocal Raman imaging and ATR-FTIR spectroscopy

Abstract: Bacterial and abiotic decay in waterlogged archaeological Picea abies (L.) Karst studied by confocal Raman imaging and ATR-FTIR spectroscopyAbstract: Waterlogged archaeological Norway spruce [Picea abies (L.) Karst] poles were studied by means of confocal Raman imaging (CRI) and attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) analysis to determine lignin and polysaccharide composition and distribution in the cell wall. The waterlogged archaeological wood (WAW) was submerged under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 48 publications
(61 reference statements)
1
25
0
Order By: Relevance
“…The dramatic intensity decline at both 1730 cm −1 and 1234 cm −1 indicated the loss of carboxyl groups in glucuronic acids of O-acetyl-(4-O-methylgulcurono) xylan, which was also proved by the absence of signal 16 at 21 ppm and signal 1 at 172 ppm, ascribed to CH 3 -COO-methyl carbon in hemicellulose acetyl groups and the carbonyl of carbohydrates, respectively, in the 13 C solid state NMR curve of WAW [17,[23][24][25] ( Figure 4A and Table S2). The loss of carboxyl group of glucuronic acid residues in hemicellulose probably indicates the partial loss of unconjugated ester linkages in lignin-carbohydrate complexes (LCCs) of VICWs in archaeological wood according to a previous report [14]. It is known that the covalent link between the carboxyl group of glucuronic acid residue in hemicelluloses and α-hydroxyl group of the lignin represents one kind of covalent links in LCCs [26,27].…”
Section: The Deterioration Of Cell Wall Componentsmentioning
confidence: 89%
See 2 more Smart Citations
“…The dramatic intensity decline at both 1730 cm −1 and 1234 cm −1 indicated the loss of carboxyl groups in glucuronic acids of O-acetyl-(4-O-methylgulcurono) xylan, which was also proved by the absence of signal 16 at 21 ppm and signal 1 at 172 ppm, ascribed to CH 3 -COO-methyl carbon in hemicellulose acetyl groups and the carbonyl of carbohydrates, respectively, in the 13 C solid state NMR curve of WAW [17,[23][24][25] ( Figure 4A and Table S2). The loss of carboxyl group of glucuronic acid residues in hemicellulose probably indicates the partial loss of unconjugated ester linkages in lignin-carbohydrate complexes (LCCs) of VICWs in archaeological wood according to a previous report [14]. It is known that the covalent link between the carboxyl group of glucuronic acid residue in hemicelluloses and α-hydroxyl group of the lignin represents one kind of covalent links in LCCs [26,27].…”
Section: The Deterioration Of Cell Wall Componentsmentioning
confidence: 89%
“…It should be emphasized that the Raman region from 1420 cm −1 to 1510 cm −1 was not taken into account due to the influence of the embedding material PEG. The lignin specific band at 1660 cm −1 , attributed to the conjugated C=C stretching of coniferyl alcohol or the C=O stretch of coniferaldehyde [14,36,37] (Table S4), exhibited substantial differences. CW and CML spectra of WAW revealed decrease of this respective band.…”
Section: The Deterioration Of Cell Wall Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, next to the deterioration of cellulose and hemicellulose, the modification of lignin may also lead to an increase of adsorbent functional groups in WAW [7,54,69], responsible for an increased uptake of water vapor. In detail, lignin in archaeological wood generally undergoes modifications such as the partial breakage of β-O-4 interlinks, an alternation of lignin structure, and demethylation/demethoxylation [7,54,70,71]. Although there is few studies on the relationship between WAW and the number of available OH groups, it was reported that the amount of available OH groups of delignified wood increased with the degree of delignification [29].…”
Section: The Chemical Deterioration and Increased Hydroxyl Accessibilmentioning
confidence: 99%
“…A further drawback of these studies is the assumption that the content of the wood component used as an internal standard is constant. This assumption does not hold true for most AW, as one of the major constituents of wood, cellulose, may, as a consequence of microbial decay, vary as much as to make up one third of the dry weight to approach almost complete depletion (Rowell et al 2013;Pedersen et al 2015).…”
Section: Introductionmentioning
confidence: 99%